PENGARUH KADAR HEMATOLOGI DENGAN BERAT BADAN BAYI BARU LAHIR PADA IBU DENGAN PRE EKLAMSIA DI RS MARGONO SOEKARDJO PURWOKERTO 2016 - ., Sumarni; Suryani, Evi Sri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Pre-eclampsia is one of the causes of maternal mortality. Pre-eclampsia causes a decrease in the function of a number of organs and systems is expected due to vascular endothelial dysfunction and vasospasm. Decreased organ function causes changes in pregnancy is one of them changes hematological profile of pregnant women. Preeclampsia is a significant cause of low birth weight babies. This type of research: descriptive analytic research with retrospective case control approach. Population that were pregnant women who visit and or refer to hospital Margono Soekardjo in 2015 as many as 230 people. Samples were taken by simple random sampling a total of 70 samples. Data was analyzed by T test. The results showed There was significant effect between maternal blood profile that was hemaglobin, hematocrit and erythrocyte weight newborns whereas there was no effect between leukocyte with newborn weight in pregnant women with pre-eclampsia. Conclusions: There was significant effect between the levels of hemoglobin, hematocrit and erythrocytes with newborn weight in pregnant women with pre-eclampsia in RS Margono Soekardjo Purwokerto. Keywords: hematological profile, weight newborns, pre-eclampsia